Big and broad social data and the sociological imagination: A collaborative response. Issue 2 (4th August 2014) - Housley, William; Procter, Rob; Edwards, Adam; Burnap, Peter; Williams, Matthew; Sloan, Luke; Rana, Omer; Morgan, Jeffrey; Voss, Alex; Greenhill, Anita
In this paper, we reflect on the disciplinary contours of contemporary sociology, and social science more generally, in the age of 'big and broad' social data. Our aim is to suggest how sociology and social sciences may respond to the challenges and opportunities presented by this 'data deluge' in ways that are innovative yet sensitive to the social and ethical life of data and methods. We begin by reviewing relevant contemporary methodological debates and consider how they relate to the emergence of big and broad social data as a product, reflexive artefact and organizational feature of emerging global digital society. We then explore the challenges and opportunities afforded to social science through the widespread adoption of a new generation of distributed, digital technologies and the gathering momentum of the open data movement, grounding our observations in the work of the Collaborative Online Social Media ObServatory (COSMOS) project. In conclusion, we argue that these challenges and opportunities motivate a renewed interest in the programme for a 'public sociology', characterized by the co-production of social scientific knowledge involving a broad range of actors and publics.